(untitled) (مجلة إحالات, 2025)
ملخص : هذا العمل موسوم " شرح المقدمة الاجرومية بين المسائل التحقيقية للشيخ اطفيش و التحفة السّنية للشيخ محمد محي الدين عبد الحميد " نحاول من خلاله عرض موازنة للعملين من جهة المنهج و المضمون ، ملتزمين فيه الموضوعية التامة ،لنخلص في الاخير ببعض النتائج ، والتي من أهمها وجوب العودة الى التراث الجزائري الثمين الذي يبقى حبيس المكتبات الخاصة . :المقدمة الآجرومية ، مسائل التحقيقية ، التحفة السّنية ، الموازنة . الكلمات المفتاحية Abstract The recent study deel with a comparison between tow works , one of theme is algerian belongue from « Mohammed Ibn Yocef Itfaiach entitled » » Al massail attahhkikia fi atohfa al ajaromia » and the other work belongue from Egypt by « Mohammed Mohyi Eddine » entitled « Attohfa Assania ». our work focus on two point the simmilarities and the differences on the structure of the works(format) and the content. We dealt with this work objectively, and we conclude in the end that the Algerian linguistic heritage should be studied . Key words ; Comparison (simmilarities& the differences), Al massail attahhkikia fi atohfa al ajaromia, Attohfa Assania.